Seleção de localidades com potencial para receber investimentos em infraestrutura aeroportuária : um estudo de caso da aviação regional - Vasconcelos, Hugo Vieira de (2018)
This study develops a model for the selection of Brazilian municipalities with potential to receive investments in airport infrastructure, as a way to foment regional aviation and to increase Brazilian population access to regular domestic flights. For this purpose, discrete covering based facilities location models were used. A model was developed based on partial coverage and with restrictions on the installation of nearby facilities. The results show the contribution of the proposed model when compared to the classic coverage location problem and also when compared to the Brazilian Regional Aviation Development Program, indicating the possibility of reducing considerably the number of airports contemplated by investments, maintaining the same level of coverage of the population.